Tingkat Kepuasan Dosen Terhadap Layanan Pelatihan - Albertha Lolo Tandung; Obet Lumajang Bijang; Paulus Banto (Politeknik Pelayaran Barombong, 2021)
This study aims to determine the level of lecturer satisfaction obtained during the training. Training participants' satisfaction in the learning process is highly dependent on this research. Training participants' satisfaction in the learning process is very dependent on the resource person, the learning process in accordance with the expectations of the training participants is a reflection of the competence level of the resource person. The research approach is descriptive quantitative, the population in this study were training participants who attended the training and the sampling technique used in this study was purposive sampling. The data collection method used was a questionnaire method using a Likert scale, statistical analysis using Microsoft Excel. The results of the analysis of the level of satisfaction of lecturers with training services are measured based on the dimensions of physical form (tangible), reliability (realibility), responsiveness (responsiveness), assurance (assurance) and empathy (empathy) Based on the percentage and score scores have been obtained satisfaction with training services in providing training . The lecturers' assessment of the training service falls into the satisfactory category so that the tangibles and reliability aspects meet the expectations of the lecturers.